Simplified Assessment of Antiretroviral Adherence and Prediction of Virological Efficacy in HIV-Infected Patients in Cambodia - Segeral, Olivier; Madec, Yoann; Ban, Boroath; Ouk, Vara; Hak, Chan Roeurn; Le Tiec, Clotilde; Nerrienet, Eric; Goujard, Cécile; Taburet, Anne Marie; Delfraissy, Jean Francois; Fontanet, Arnaud (AIDS Research and Treatment, 2010)
Background. Adherence to antiviral therapy is important for HIV-infected people living in low- and middle-income countries, because of poor access to alternative regimens. Methods. We conducted a cross-sectional survey of adherence in Cambodian patients enrolled in the ESTHER program and treated with WHO first-line regimen for at least 6 months. The survey was based on a self-report questionnaire, drug assay, MCV measurement, visual analog scale, and viral load HIV RNA. Results. Two hundred fifty-nine patients treated for a median of 16 months participated in the survey. At inclusion in the program, 158 patients (61%) were ARV-naïve. The virological success rate was 71% overall and 81% in previously ARV-naive patients. Considered individually, the measures suggested perfect adherence in 71% to 93% of patients. In multivariate analysis adjusted for sex and therapeutic status before HAART initiation, only the biological markers were associated with virological efficacy. Self-funded treatment before entry to the program was highly predictive of virological failure. Conclusion. Adherence was excellent in these Cambodian patients. Biological markers were predictive of virological efficacy. MCV might thus serve as a simple alternative for assessing adherence and predicting virological efficacy among patients receiving AZT- or d4T-based regimens.